Preclinical and clinical pharmacokinetic/pharmacodynamic considerations for antibody–drug conjugates. Issue 5 (September 2013) - Sapra, Puja; Betts, Alison; Boni, Joseph
Antibody-drug conjugates (ADCs) represent a promising therapeutic modality for the clinical management of cancer. Here we discuss the clinical pharmacology and safety of ADCs that are either approved or in late stages of clinical development. We have taken examples of ADCs employing either DNA damaging payloads (such as calicheamicin) or tubulin depolymerizing agents (such as auristatins and maytansinoids) to discuss the impact of dose and dosage intervals on pharmacokinetics/pharmacodynamics (PK/PD) and safety of ADCs. We also discuss the development of PK/PD models that were validated using preclinical and clinical data from two approved ADCs (ado-trastuzumab emtansine (T-DM1, Kadcyla™) and brentuximab vedotin (SGN-35, Adcetris™). These models could be used to predict clinical efficacious doses of ADCs.